Modulation of Hippocampal Circuits by Muscarinic and Nicotinic Receptors - Dannenberg, Holger; Young, Kimberly; Hasselmo, Michael (Frontiers in Neural Circuits, 2017)
This article provides a review of the effects of activation of muscarinic and nicotinic receptors on the physiological properties of circuits in the hippocampal formation. Previous papers have described detailed computational hypotheses about the role of cholinergic neuromodulation in enhancing the dynamics for encoding in cortical structures and the role of reduced cholinergic modulation in allowing consolidation of previously encoded information. This paper will focus on addressing the broad scope of different modulatory effects observed within hippocampal circuits, highlighting the heterogeneity of cholinergic modulation in terms of the physiological effects of activation of muscarinic and nicotinic receptors and the heterogeneity of effects on different subclasses of neurons.